Safety of daily administration of pellets containing parasiticidal fungal spores over a long period of time in heifers. Issue 11 (2nd November 2022) - Voinot, M.; Arroyo, F.; Hernández, J. Á.; Paz-Silva, A.; Sánchez-Andrade, R.; Bermúdez, R.; Guillot, J.; Madeira de Carvalho, L. M.; Arias, M. S.; Cazapal-Monteiro, C. F.
ABSTRACT: The innocuousness of the prolonged ingestion of commercial nutritional pellets containing spores of the fungal species Mucor circinelloides and Duddingtonia flagrans on grazing dairy heifers was tested. During two years, one group (G-F) received daily 2.5 kg pellets with 3 × 10 5 spores each fungus / kg pellet, and group G-C without them. In the third year, ruminants in both groups received spore-free feed. Evaluation of red and white blood cell parameters (RBC and WBC, respectively) was performed monthly. Alterations on the digestive activity, respiratory function and reproductive functionality were also recorded. Three heifers of G-F were necropsied in the second year of study and four in the third. Samples collected from different tissues and organs were preserved in 10% neutral buffered formalin, sections included in paraffin and stained with haematoxylin/eosin, periodic acid Schiff, Fontana–Masson and Ziehl–Neelsen. During the first two years, normal numbers of RBC and WBC were recorded in G-F, by values of RBC and haemoglobin (HB) below physiological standards in G-C. No differences between the two groups were obtained in the third year, with RBC and HB levels lower than normal (physiological). No fungal structures or lesions related to fungal administration were visualised in the tissues of G-F. It is concluded that the daily ingestion of pellets containing spores of the parasiticidal fungi M. circinelloides and D. flagrans over a long period of time is completely safe.